2010
DOI: 10.1016/j.chom.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Functional Analysis of Plasmodium Protein Kinases Identifies Essential Regulators of Mosquito Transmission

Abstract: SummaryAlthough eukaryotic protein kinases (ePKs) contribute to many cellular processes, only three Plasmodium falciparum ePKs have thus far been identified as essential for parasite asexual blood stage development. To identify pathways essential for parasite transmission between their mammalian host and mosquito vector, we undertook a systematic functional analysis of ePKs in the genetically tractable rodent parasite Plasmodium berghei. Modeling domain signatures of conventional ePKs identified 66 putative Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
393
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(414 citation statements)
references
References 61 publications
16
393
2
3
Order By: Relevance
“…In comparison, a recent study of 66 ePKs of the rodent malaria parasite P. berghei identified 43 protein kinases that are refractory to deletion in the blood stage and 23 whose genes could be deleted 37 (Supplementary Table S1). Although there is overall a good level of agreement between the ePKs identified as essential in the mouse parasite and those we identify here to be have a crucial role in P. falciparum (Supplementary Table S1), there are nevertheless differences, which may underlie divergence between human and mouse malarial species resulting from a split estimated to have occurred 70 million years ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, a recent study of 66 ePKs of the rodent malaria parasite P. berghei identified 43 protein kinases that are refractory to deletion in the blood stage and 23 whose genes could be deleted 37 (Supplementary Table S1). Although there is overall a good level of agreement between the ePKs identified as essential in the mouse parasite and those we identify here to be have a crucial role in P. falciparum (Supplementary Table S1), there are nevertheless differences, which may underlie divergence between human and mouse malarial species resulting from a split estimated to have occurred 70 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is overall a good level of agreement between the ePKs identified as essential in the mouse parasite and those we identify here to be have a crucial role in P. falciparum (Supplementary Table S1), there are nevertheless differences, which may underlie divergence between human and mouse malarial species resulting from a split estimated to have occurred 70 million years ago. We emphasise here that formal demonstration that a given ePK gene is not essential for asexual schizogony requires analysis of clones from the populations displaying evidence for gene disruption or deletion; this has been achieved for the entire P. berghei kinome 37 but thus far only partially in P. falciparum.…”
Section: Discussionmentioning
confidence: 99%
“…P . berghei parasites lacking the protein kinase PK7 or the cyclin G‐associated kinase GAK show severely reduced ookinete numbers (Tewari et al ., 2010). Further, deletion of the Shewanella‐like protein phosphatase (SHLP1), PPM2 or the kelch‐like domain‐containing phosphatase PPKL results in impaired P .…”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%
“…This revealed essential functions of a MAPK (Pbmap-2) and a CDPK (PbCDPK4) in male gametogenesis [29,46,47], of two NIMA-related kinases in meiosis in the mosquito vector [48,49], and of a CDK in asexual proliferation in erythrocytes [50]. This approach culminated in a kinome-wide study demonstrating that 23 P. berghei ePKs are redundant for asexual erythrocytic parasite development in mice and identifying phenotypes in sexual development for a number of these 23 ePKs [51]. A similar strategy in P. falciparum identified roles for an orphan kinase in proliferation rate linked to the number of progeny merozoites per schizont [36], for an eIF2a kinase in response to starvation stress, similar to GCN2, its closest homologue in yeast [52], and for CDPKs in motility during invasion [53] or egress of merozoites from the erythrocyte [54], to cite a few specific studies; more recently, a kinome-wide approach [19] identified 36 ePKs as refractory to gene disruption, and thus as likely crucial players in asexual proliferation in erythrocytes.…”
Section: E C To C a R P U S S Il Ic U Lo S U S T H A L A S S I O S I mentioning
confidence: 99%